PROSPEK MANAJEMEN BERBASIS DIGITAL DALAM MENINGKATKAN EFISIENSI ADMINISTRASI PENDIDIKAN DI SMP NEGERI 1 PAMIJAHAN - Atik Hermawati; Ima Rahmawati; Muhzir Ihsan (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2026)
This study reveals various challenges faced in administrative management at SMP Negeri 1 Pamijahan, particularly related to work efficiency and effectiveness. With the advancement of information technology, the use of digital systems has become a promising solution to improve data management in schools. The main objective of this research is to explore the potential implementation of digital management in enhancing administrative efficiency at SMP Negeri 1 Pamijahan. The research method used is a qualitative approach, with data collected through direct interviews with the principal, teachers, and administrative staff. In addition, direct observations of the administrative processes were also conducted in the field. The results of the study show that the implementation of a digital-based management system can significantly save data processing time and improve the accuracy of administrative data. From this research, it can be concluded that the adoption of digital management not only enhances administrative efficiency but also has the potential to improve the overall quality of educational services. Thus, SMP Negeri 1 Pamijahan can serve as a model in integrating digital technology for more effective administrative management. However, the implementation of this system has not yet been fully applied across all areas of the school’s educational administration. Keywords: administrative efficiency; digital management; education; junior high school.